Gravity model estimation: Fixed effects vs. random intercept poisson pseudo maximum likelihood; Gravity Modell Schätzung: Fixed Effects vs.Random Intercept Poisson Pseudo Maximum Likelihood - Sören Prehn; Bernhard Brümmer; Thomas Glauben (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
Since the work of FEENSTRA (2002), the standard ANDERSON & VAN WINCOOP (2003) Gravity Model has been estimated using a fixed effects approach. However, a fixed effects approach has a major drawback: it does not allow for the estimation of exporter- and importer-invariant variables. Thus, economically relevant variables such as exporter and importer gross domestic product are disregarded. Here, we propose a random intercept model to address this gap. This approach not only provides identical estimates to a fixed effects approach, but also allows for the estimation of exporter- and importer-invariant variables. – – Seit FEENSTRA (2002) wird das Standard ANDERSON & VAN WINCOOP (2003) Gravity Modell mittels Fixed-Effects-Ansatzes geschätzt. Der Fixed-Effects-Ansatz hat allerdings den entscheidenden Nachteil, dass er nicht die Schätzung von Exporteur- und Importeur-invarianten Variablen erlaubt. Folglich lassen sich ökonomisch relevante Variablen wie Exporteur- und Importeur-Bruttosozialprodukt nicht berücksichtigen. Wir empfehlen ein Random-Intercept-Modell anstatt. Dieser Ansatz liefert nicht nur die identischen Schätzer wie ein Fixed-Effects-Modell, sondern erlaubt auch die Schätzung von Exporteur- und Importeur-invarianten Variablen.
urn:nbn:de:gbv:3:2-28709
Keywords: F1; C3; 330; Gravity Model Estimation; Poisson Pseudo Maximum Likelihood; Fixed Effects Model; Random Intercept Model